A Novel Scoring System for Small Artery Disease and Medial Arterial Calcification Is Strongly Associated With Major Adverse Limb Events in Patients With Chronic Limb-Threatening Ischemia. (April 2021) - Ferraresi, Roberto; Ucci, Alessandro; Pizzuto, Alessandra; Losurdo, Fabrizio; Caminiti, Maurizio; Minnella, Daniela; Casini, Andrea; Clerici, Giacomo; Montero-Baker, Miguel; Mills, Joseph
Purpose: To evaluate the roles of small artery disease (SAD) and medial arterial calcification (MAC) in patients with chronic limb-threatening ischemia (CLTI) and to identify any correlation between these factors and peripheral artery disease (PAD) or outcomes after treatment. Materials and Methods: A retrospective review was conducted of 259 limbs with tissue loss among 223 CLTI patients (mean age 72.2±11.4 years; 194 men) having an angiographic foot vessel study, foot radiography, and at least 6 months of follow-up after intervention. SAD and MAC were quantified using a 3-level score (0=absent, 1=moderate, 2=severe) based on angiography for SAD and foot radiographs for MAC. The MAC score was validated and compared with the SAD score, evaluating their associations with PAD distribution and clinical outcomes. Results: Based on the MAC score, the 259 limbs were classified as 55 group 0 (21.2%), 89 group 1 (34.4%), and 115 group 2 (44.4%). The SAD score stratified the 259 limbs as 67 group 0 (25.9%), 76 group 1 (29.3%), and 116 group 2 (44.8%). Interobserver reproducibility of the MAC score was high (correlation coefficient 0.96). Sensitivity and specificity of the MAC score in detecting SAD was 100% and 98.1%, respectively, in SAD groups 0 and 2 vs 99.1% and 92.7%, respectively, for SAD group 1. PAD was more proximal in MAC and SAD groups 0 and more distal in groups 1 and 2. Both MAC and SAD scores were able to predict clinical endpoints. Multivariable analysis demonstrated that the MAC score represents an independent risk factor for adverse limb events. Conclusion: SAD and MAC must be considered expressions of the same obstructing disease, able to adversely impact the fate of CLTI patients. SAD and MAC scores are powerful prognostic indicators of major adverse limb events in CLTI patients.